Risk factors for depression among elderly in Bangalore urban district: a case control study - N. R., Ravindra; M. R., Rashmi; Maheswaran, R. (International Journal Of Community Medicine And Public Health, 2017)
Background: With a rapidly aging society, geriatric mental health is emerging as an important public health concern. According to the WHO, prevalence of depression in adults aged ≥60 years in developed and developing countries was 0.5 million and 4.8 million respectively in 2004. The objective of this study is to estimate the prevalence of depression and to assess risk factors of depression among elderly in an urban population. Methods: A case control study was conducted in May-June 2016 in the Bagalgunte area in Bangalore urban district. Purposive sampling technique was employed and all elderly persons (≥60 years) residing in that area were included. Participants were assessed for depression using validated 15 item (short version) geriatric depression scale (GDS).Those with GDS score >5 were considered as cases and those with GDS score ≤5 as controls. Final sample size was 201. Study variables included socio-demographic parameters and all possible risk factors of depression. Results: Of the 201 respondents interviewed, 90 (44.8%) were cases and 111 (55.2%) were controls. 159 (79.1%) were aged 60–69 years and 116 (58%) were male. Low socioeconomic status, elderly who were living alone (single/divorced/death of spouse), h/o dependency on others for daily living, negligence, abuse, economic loss in last 5 years, substance abuse, change of residence, insomnia and anorexia were found to be significantly associated with depression among elderly. Conclusions: In this study, depression among elderly was found to be high. These study findings can help programme managers to focus on mental health of elderly and implement practical and comprehensive strategiesand timely interventions to promote mental health and prevent depression.